Social Vulnerability towards Covid-19 Cases in Palembang City: A Spatial Analysis in Indonesia - Marisa Nurhaliza; Amrina Rosyada (Al-Sihah : The Public Health Science Journal, 2022)
Social vulnerability is defined as a characteristic of groups that can threaten their ability to prevent, cope with or recover from the impact of a hazard. By linking social conditions with risk exposure, social vulnerability is useful for looking at the inequality of the social effects experienced by society from health crises such as the Covid-19 pandemic. The purpose of this study was to spatially analyze the vulnerability to Covid-19 in the Palembang City sub-district in 2021 by using the social characteristics of the region. This type of research was descriptive with an ecological study design. The population group studied was 18 sub-districts in the city of Palembang. The study used secondary data such as the Covid-19 variable and the vulnerable population received from the Palembang City Health Office, and the rest of the variable from the government's official website and Google Maps. The analysis process was done through Spatial Multi-Criteria Evaluation (SMCE) using Microsoft Excel and spatial analysis in weighted overlays using QGIS. For the final social vulnerability status, sub-districts with high vulnerability were Sukarami, Ilir Barat I, Plaju, and Ilir Timur I, respectively. For sub-districts with low vulnerability were Bukit Kecil and Sematang Borang. One way to reduce the level of vulnerability in an area was by taking preventive measures in the community whose needs needed to be further considered and maximizing the implementation of 3T activities and vaccinations.